PEMANFAATAN ICT DALAM PENINGKATAN KOMPETENSI PEDAGOGIK DAN PENGARUHNYA TERHADAP SERTIFIKASI GURU SEKOLAH MENENGAH PERTAMA ACEH BARAT - Mulia Mulia (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
The ability to determine learning resources/media/teaching aids is an indicator of pedagogical competence that must be possessed by every educator. There are teachers in the implementation of teaching and learning are still lacking in developing media. This quantitative research has two variables, namely the independent variable (X) and the dependent variable is (Y), to find the effect of variable X on the variable Y the author uses a simple linear regression test. The population in this study were certification teachers at West Aceh Junior High School. The data collection techniques of this study, to see the Pedagogical competence of teachers using interview techniques, while to see the effect of certification on the pedagogical competence of teachers using a questionnaire technique. The results of this study The teacher utilizes information and communication technology for the benefit of organizing learning activities that educate, how to facilitate the development of potential learners to actualize the various potentials they have, and how to evaluate learning by giving tests directly both in writing and orally at the end of each meeting. Based on the calculation of the results of data analysis, there is a relationship/correlation between teacher certification and teacher pedagogical competence, while the direction of correlation is positive between teacher certification and teacher pedagogical competence.